Students’ Fear in Presenting Assignments in the Classroom - Paudel, Shiva Prasad (Dhaulagiri Journal of Contemporary Issues, 2023)
This action research focuses on exploring the Psychological behaviors of students’ fear in presenting assignments in the classroom of BED first year students at Dhawalagiri Multiple campus of Tribhuvan University in Nepal. It investigates the factors contributing to students’ fear of presenting assignments, fear on academic performance and personnel l well-being, and potential interventions to reduce anxiety and improve student outcomes. The research reviews the historical evolution of studies from twentieth century to onwards on the fear of presenting assignments and examines the factors that contribute to this fear, including like physiological, psychological, cognitive, behavioral, environmental, and technological factors. The study adopts a mixed-methods approach, combining qualitative and quantitative data collection techniques such as interviews and observations. Based on the findings, multiple interventions are implemented, including workshops, mentoring, and changes in assessment practices, to address the identified factors and reduce fear. The effectiveness of these interventions is continuously monitored and evaluated. The research aims to provide insights and recommendations to create a supportive and empowering classroom environment for students, promoting their academic success and well-being.